2019
DOI: 10.3390/su11143806
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation Strategies for Reduction of Embodied Energy and Carbon, in the Construction Systems of Contemporary Quality Architecture

Abstract: The criticality related to the consumption of operational energy and related greenhouse gas (GHG) emissions of existing buildings is clearly decreasing in new buildings due to the strategies tested and applied in recent years in the energy retrofit sector. Recently, studies have been focusing on strategies to reduce environmental impacts related to the entire life cycle of the building organism, with reference to the reduction of embodied energy (and related greenhouse gas emissions) in building materials. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…related to reductions in environmental pressures resulting from the dynamics hypothesised for the development of the experimental model (mod.2). It is evident, in fact, that the latter approach has a lower impact in terms of exploitation of primary resources [18], as well as in terms of reduction of CO 2 emissions [19][20].…”
Section: Discussionmentioning
confidence: 99%
“…related to reductions in environmental pressures resulting from the dynamics hypothesised for the development of the experimental model (mod.2). It is evident, in fact, that the latter approach has a lower impact in terms of exploitation of primary resources [18], as well as in terms of reduction of CO 2 emissions [19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Table 6 shows the amounts of energy saved at the production, construction, and EOL stages of a building life cycle, along with representing the percentage of energy saved throughout the entire building life cycle by recycling or reusing materials (detailed data on energy saving were available for five studies). Reusing and recycling building materials has already been suggested as an effective strategy to mitigate energy use in the building life cycle by decreasing embodied energy [8,62]. Based on Table 6, it can be observed that this strategy led to the reduction of total building life cycle energy use by the range of 5% to 22%.…”
Section: Reuse and Recycling Potentialsmentioning
confidence: 98%
“…According to a study on prefabrication methods, the dry building system (with a metal or wood bearing structure) is the most functional design solution. It has emerged that the gap between the construction sector and the mass production industries can be compensated by the adoption of an off-site construction process [101,105]. The construction system in CLT perfectly meets these requirements.…”
Section: Characteristic Properties Of Clt Systemsmentioning
confidence: 99%